Influence of recovery duration during 6-s sprint interval exercise on time spent at high rates of oxygen uptake - Shia, Q.; Tong, T. K.; Sun, S.; Kong, Z.; Chan, C. K.; Liu, W.; Nie, L. (Journal of Exercise Science & Fitness, 2019)
This study examined whether time spent at high rates of oxygen consumption (VO2) during 6-s sprint interval exercises (SIE) is a function of recovery interval duration. Methods: In a randomised crossover study, thirteen male endurance runners performed 40 × 6-s all-out sprints interspersed with 15-s, 30-s and 60-s passive recovery intervals (SIE15, SIE30, and SIE60 trials respectively), and a work duration-matched Wingate-SIE (8 × 30-s all-out sprints with 4-min passive recovery, SIEWin trial). The accumulated exercise time at = 80%, 85%, 90%, 95% and 100% of VO2max, and maximum heart rate (HRmax) in the four trials were compared. Results: During the 6-s SIEs, accumulated time spent at all selected high rates of VO2max increased as recovery time decreased, whilst the SIE work rate decreased (p < .05). In SIEWin, although the exercise lasted longer, the time spent at =90% VO2max (74 ± 16 s) was significant less than that in SIE15 (368 ± 63 s, p < .05), yet comparable to that in SIE30 (118 ± 30 s, p > .05), and longer than that in SIE60 (20 ± 14 s, p < .05). The differences between the four trials in accumulated time at high percentages of HRmax were similar to those for VO2, although the temporal characteristics of the increases in HR and VO2 during the SIEs were different. Conclusion: In conclusion, the duration of the recovery interval in 6-s SIE protocols appears to be a crucial parameter when sprint interval training is prescribed to enhance aerobic capacity. Further, the SIE15 protocol may represent a potential alternative to 30-s SIEWin in the development of time-efficient aerobic training intervention.